Pitx3 deficient mice as a genetic animal model of co-morbid depressive disorder and parkinsonism - Kim, Kyoung-Shim; Kang, Young-Mi; Kang, Young; Park, Tae-Shin; Park, Hye-Yeon; Kim, Yoon-Jung; Han, Baek-Soo; Kim, Chun-Hyung; Lee, Chul-Ho; Ardayfio, Paul A.; Han, Pyung-Lim; Jung, Bong-Hyun; et al. (Brain research, 2014)
Approximately 40–50% of all patients with Parkinson׳s disease (PD) show symptoms and signs of depressive disorders, for which neither pathogenic understanding nor rational treatment are available. Using Pit3x-deficient mice, a model for selective nigrostriatal dopaminergic neurodegeneration, we tested depression-related behaviors and acute stress responses to better understand how a nigrostriatal dopaminergic deficit increases the prevalence of depressive disorders in PD patients. Pitx3-deficient mice showed decreased sucrose consumption and preference in the two-bottle free-choice test of anhedonia. Acute restraint stress increased c-Fos (known as a neuronal activity marker) expression levels in various brain regions, including the prefrontal cortex, striatum, nucleus accumbens, and paraventricular nucleus of the hypothalamus (PVN), in both Pitx3+/+ and −/− mice. However, the stress-induced increases in c-Fos levels in the cortex, dorsal striatum, and PVN were significantly greater in Pitx3−/− than +/+ mice, suggesting that signs of depressive disorders in parkinsonism are related to altered stress vulnerability. Based on these results, we propose that Pitx3−/− mice may serve as a useful genetic animal model for co-morbid depressive disorder and parkinsonism. •Pitx3-deficient mice showed depression-like signs in the test of anhedonia.•Stress-induced c-Fos expression levels in brain were abnormally increased in Pitx3−/− mice.•Stress hormone levels were higher in Pitx3−/− than wild-type mice after acute stress.